2016
DOI: 10.1080/15459624.2016.1179386
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of tabs on filtering facepiece respirator straps to increase proper doffing techniques while reducing contact transmission of pathogens

Abstract: NIOSH-certified N95 filtering facepiece respirators (FFRs) are used in healthcare settings as a control measure to mitigate exposures to airborne infectious particles. When the outer surface of an FFR becomes contaminated, it presents a contact transmission risk to the wearer. The Centers for Disease Control and Prevention (CDC) guidance recommends that healthcare workers (HCWs) doff FFRs by grasping the straps at the back of the head to avoid contact with the potentially contaminated surface. Adherence to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…[11] Images of the subjects’ hands were captured under UV-A light using a Nikon DSLR camera (Nikon Corp., Japan) from a fixed distance of 20 cm. Images were imported into Image J software and analyzed using the Lasso tool to delineate the zone of visual and measure the surface area of contamination.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Images of the subjects’ hands were captured under UV-A light using a Nikon DSLR camera (Nikon Corp., Japan) from a fixed distance of 20 cm. Images were imported into Image J software and analyzed using the Lasso tool to delineate the zone of visual and measure the surface area of contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PPE effectively prevents contact and droplet transmission; however, in the context of aerosol and airborne transmission, PPE is not as efficient. 20 , 65 , 66 , 71 The strength of this systematic review is the primary focus on human-generated aerosol particle size and distribution, evidence of aerosol transmission of infectious disease, and PPE's efficacy. Although the present literature review has performed its due diligence in synthesizing information on the aerosol transmission of infectious disease and PPE efficacy, a few limitations should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, healthcare workers thought respirators with tabs were easier to remove than those without tabs and they were significantly less likely to contaminate themselves with a tracer when removing the respirators with tabs than those without tabs. These results suggest that the tabs may be a good addition to respirator straps but healthcare workers must be taught to use them properly [126].…”
Section: Designing and Using Personal Protective Equipmentmentioning
confidence: 96%
“…For example, study by AlGharmri et al [125] found that full-face, negative pressure respirators impaired users' motor, visual, and cognitive abilities and were associated with an increased error rate. Strauch et al [126] put tabs on respirator straps to help healthcare workers remove these devices safely. The investigators noted that "use of the tabs was not intuitive."…”
Section: Designing and Using Personal Protective Equipmentmentioning
confidence: 99%